1994
DOI: 10.1143/jjap.33.l331
|View full text |Cite
|
Sign up to set email alerts
|

Novel Preparation Method of Metal Particles Dispersed in Polymer Films and Their Third-Order Optical Nonlinearities

Abstract: Polymer films containing nanometer-sized particles of Ag or Au were prepared by a simple process based on the reduction of organometallic compounds in a polymer matrix. Films were formed by casting a polymer solution admixed with an organometallic compound and a reducing agent onto a substrate. Third-order optical susceptibilities, χ(3), of these films were measured to be 2×10-9 esu for Ag and 1×10-8 esu for Au.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 6 publications
0
39
0
Order By: Relevance
“…Therefore, at this optical frequency p, (3) eff( ) of the nano-composite can overtake giant values as a result of the enhancement reinforced by the power 4 of the form factor f( ) compared to those found in classical bulk materials. Degenerate four-wave mixing as well as Z-scan measurements in Ag and Au as well as Cu based nanocomposites consistently revealed the colossal third order nonlinear optical susceptibilities (3) eff( ) of about 10 -7 -10 -9 esu in the vicinity of the surface plasmon resonance, with response times of the order of picoseconds, Table 1, (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). This enhanced (3) eff( ) offered by this new class of nanocomposites is opening new perspectives in emerging nanophotonics sector.…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, at this optical frequency p, (3) eff( ) of the nano-composite can overtake giant values as a result of the enhancement reinforced by the power 4 of the form factor f( ) compared to those found in classical bulk materials. Degenerate four-wave mixing as well as Z-scan measurements in Ag and Au as well as Cu based nanocomposites consistently revealed the colossal third order nonlinear optical susceptibilities (3) eff( ) of about 10 -7 -10 -9 esu in the vicinity of the surface plasmon resonance, with response times of the order of picoseconds, Table 1, (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). This enhanced (3) eff( ) offered by this new class of nanocomposites is opening new perspectives in emerging nanophotonics sector.…”
Section: Introductionmentioning
confidence: 81%
“…In biology and biochemistry, nanoparticles have attracted much attention. Especially, PNPs with size in the range of 10 to 50 nm are most attractive for practical reasons [2][3][4][5][6]. Cancer killed 7.9 million people worldwide in 2007 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the absorption maximum for the SPR peak of Ag nanoparticles in films are observed at 410 nm. 6,[8][9][10][11][12] Accordingly, the observance of SPR peaks indicated that the size of the Ag nanoparticles are much smaller than the mean free path of the electrons in bulk silver (ca. 52 nm), 20 as shown in Figure 2.…”
Section: Nylon 6/ag Compositesmentioning
confidence: 99%
“…6,8,9 Similarly as that of Au nanoparticles, it is well known that Ag nanoparticles possess interesting optical properties: for example, surface plasmon resonance (SPR) in the state of nanoparticle. 6,[8][9][10][11][12] Additionally, Ag nanoparticles in nylon 11/Ag can be converted into Ag 2 S nanoparticles by exposing to a mix- † To whom correspondence should be addressed.…”
mentioning
confidence: 99%